1986
DOI: 10.1063/1.450914
|View full text |Cite
|
Sign up to set email alerts
|

Systematic determination of MCSCF equilibrium and transition structures and reaction paths

Abstract: The restricted step optimization algorithm is applied to potential energy surfaces calculated from multiconfiguration self-consistent-field wave functions. Equilibrium and transition-state geometries are determined by iteratively solving a set of level-shifted Newton–Raphson equations. At each geometry the molecular gradient and Hessian are calculated analytically, and a first-order prediction of the wave function at the next geometry is obtained by combining the geometrical derivatives of the wave function wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Minima can be determined using first-order (quasi-Newton) and second-order (Newton) methods 41. Dalton also has several first- and second-order methods for determining saddle points (transition states), including mode following42 and image minimization 43. Geometry optimizations may be performed for excited states44,45 and core-ionized states 46.…”
Section: Molecular Propertiesmentioning
confidence: 99%
“…Minima can be determined using first-order (quasi-Newton) and second-order (Newton) methods 41. Dalton also has several first- and second-order methods for determining saddle points (transition states), including mode following42 and image minimization 43. Geometry optimizations may be performed for excited states44,45 and core-ionized states 46.…”
Section: Molecular Propertiesmentioning
confidence: 99%
“…To summarize, DALTON geometry optimizations are carried out in redundant internal coordinates 41,43 using the quasi-Newton method with the Broyden-Fletcher-GoldfarbShanno ͑BFGS͒ updating formula 53 and the initial Hessian proposed by Lindh et al 54 The steps are determined by the level-shifted trust-region method. 55 At each iteration, the root-mean-square of the gradient, its maximum absolute element, the root-mean-square of the step vector, and its maximum absolute element in internal coordinates are determined; for a chosen threshold parameter ⑀ ͑typically 10 −4 ͒, convergence is declared if these four quantities are smaller than ⑀, 5⑀, 3⑀, and 15⑀, respectively.…”
Section: F Geometry Optimizationmentioning
confidence: 99%
“…Needless to say, the true trans± cis isomerization path for the N 2 H 2 molecule is not via double bond rotation but as in-plane inversion or via partial dissociation into a N 2 H radical [45]. Using di erent theoretical methods it was found that the double bond rotation is not favourable isomerization pathway since the energy barrier about 67 kcal mol -1 is too high [45].…”
Section: Introductionmentioning
confidence: 97%